On the Brudny˘ı-Krugljak Duality Theory of Spaces Formed by the K-Method of Interpolation - Kerman, Ron; Milman, Mario; Sinnamon, Gord (Revista Matemática Complutense, 2007)
The Brudny˘ı-Krugljak duality theory for the K-method is elaborated for a class of parameters derived from rearrangement-invariant spaces. As examples, concrete expressions are given for the norms dual to certain interpolation spaces between two rearrangement-invariant spaces. These interpolation spaces are formed by the K-method using parameters related to classical Lorentz spaces or Orlicz spaces.